STRATEGI PENGUATAN INSTITUSI PENDIDIKAN TINGGI AGAMA ISLAM INDONESIA: TELAAH HISTORIS TRANSFORMASI FA-UII KE PTAIN ERA MENTERI AGAMA K.H. A. WAHID HASYIM - Darul Abror (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This paper aims to discuss the politics of strengthening Islamic higher education institutions Era Minister of Religion K.H. A Wahid Hasyim which has never been studied by anyone. So this study becomes important to do. This paper uses